2011
DOI: 10.1210/en.2010-1455
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and Dopamine Stimulate Ghrelin Secretion by the Ghrelin-Producing Cell Line, MGN3-1 in Vitro

Abstract: To understand the physiological role of ghrelin, it is crucial to study both the actions of ghrelin and the regulation of ghrelin secretion. Although ghrelin actions have been extensively revealed, the direct factors regulating ghrelin secretion by ghrelin-producing cells (X/A-like cells), however, is not fully understood. In this study, we examined the effects of peptide hormones and neurotransmitters on in vitro ghrelin secretion by the recently developed ghrelin-producing cell line MGN3-1. Oxytocin and vaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 28 publications
3
56
1
Order By: Relevance
“…Moreover, we found that the mRNA encoding the b 1 receptor was enriched .50-fold both in the cultured ghrelinoma cells and in ghrelin-secreting cells isolated from mouse stomach by fluorescence cell sorting (Zhao et al 2010b). Subsequent to our study, Iwakura et al (2011) examined the effects of 21 peptide hormones and 10 neurotransmitters on ghrelin secretion in a different ghrelinoma cell line, MGN3.1. Only three of the 31 compounds examined showed significant (i.e., greater than twofold) stimulation of ghrelin secretion: norepinephrine, epinephrine, and dopamine.…”
Section: How Do Gastric Ghrelin-secreting Cells Respond To Hypoglycemia?mentioning
confidence: 99%
“…Moreover, we found that the mRNA encoding the b 1 receptor was enriched .50-fold both in the cultured ghrelinoma cells and in ghrelin-secreting cells isolated from mouse stomach by fluorescence cell sorting (Zhao et al 2010b). Subsequent to our study, Iwakura et al (2011) examined the effects of 21 peptide hormones and 10 neurotransmitters on ghrelin secretion in a different ghrelinoma cell line, MGN3.1. Only three of the 31 compounds examined showed significant (i.e., greater than twofold) stimulation of ghrelin secretion: norepinephrine, epinephrine, and dopamine.…”
Section: How Do Gastric Ghrelin-secreting Cells Respond To Hypoglycemia?mentioning
confidence: 99%
“…Supportive of this assertion, ghrelin secretion increases when sympathetic nerves are stimulated artificially or when adrenergic agents are infused locally into the gastric submucosa (29,30). Norepinephrine, epinephrine, and isoproterenol all stimulate ghrelin secretion from ghrelinoma cell lines and from primary cultures of gastric mucosal cells (26,(31)(32)(33)(34)(35)(36). Reserpine, which depletes norepinephrine from sympathetic Ghrelin is an orexigenic gastric peptide hormone secreted when caloric intake is limited.…”
Section: Introductionmentioning
confidence: 99%
“…These results are supported by high levels of b1-adrenergic receptor expression in ghrelin cells of the stomach. Thus, sympathetic nerves stimulate directly ghrelin secretion [69][70][71][72]. According to Yang et al [73], ghrelin may regulate gastric smooth muscle contraction induced by cholinergic neurotransmitters using GHS-R1s, which are expressed on myenteric nerve cells, interstitial cells of Cajal and smooth muscle cells.…”
Section: Resultsmentioning
confidence: 99%